Chromopolarizability of Charmonium and ππ Final State Interaction Revisited - Yun-Hua Chen (Advances in High Energy Physics)
The chromopolarizability of a quarkonium describes the quarkonium’s interaction with soft gluonic fields and can be measured in the heavy quarkonium decay. Within the framework of dispersion theory which considers the ππ final state interaction (FSI) model-independently, we analyze the transition ψ′→J/ψπ+π- and obtain the chromopolarizability αψ′ψ and the parameter κ. It is found that the ππ FSI plays an important role in extracting the chromopolarizability from the experimental data. The obtained chromopolarizability with the FSI is reduced to about 1/2 of that without the FSI. With the FSI, we determine the chromopolarizability αψ′ψ=(1.44±0.02)  GeV-3 and the parameter κ=0.139±0.005. Our results could be useful in studying the interactions of charmonium with light hadrons.